2007
DOI: 10.3386/w13674
|View full text |Cite
|
Sign up to set email alerts
|

Frictional Wage Dispersion in Search Models: A Quantitative Assessment

Abstract: Standard search and matching models of equilibrium unemployment, once properly calibrated, can generate only a small amount of frictional wage dispersion, i.e., wage differentials among ex-ante similar workers induced purely by search frictions. We derive this result for a specific measure of wage dispersion-the ratio between the average wage and the lowest (reservation) wage paid. We show that in a large class of search and matching models this statistic (the "mean-min ratio") can be obtained in closed form a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
179
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(199 citation statements)
references
References 3 publications
19
179
1
Order By: Relevance
“…Multiple causes underlie this result. First, limited wage dispersion is a standard finding in well calibrated search models of the labor market, as shown by Hornstein et al (2009). Second, the high value of home production restricts the amount of wage dispersion that can arise.…”
Section: Estimation Resultsmentioning
confidence: 99%
“…Multiple causes underlie this result. First, limited wage dispersion is a standard finding in well calibrated search models of the labor market, as shown by Hornstein et al (2009). Second, the high value of home production restricts the amount of wage dispersion that can arise.…”
Section: Estimation Resultsmentioning
confidence: 99%
“…Our results are also consistent with structural estimates in van den Berg (1990) who found that most job offers are indeed accepted and that unemployed workers do not seem to reject many jobs based on wages. Similarly, Hornstein, Krusell, and Violante (2011) show that in broad classes of search models, the value of non market time -and hence the reservation wage -has to be low to be able to reconcile why despite high wage dispersion, and hence a high option value of searching, workers in practice accept jobs quickly. Following our approach, Lalive, Landais, and Zweimueller (2013) also find that the path of reemployment wages does not respond to increases in UI durations in Austria.…”
Section: Estimates Of the Shift Of Reemployment Hazards And Wagesmentioning
confidence: 99%
“…It also predicts a quantitatively accurate size-wage differential. Hornstein, Krusell, and Violante (2011) reported that standard calibrations of searchand-matching models without on-the-job search cannot generate much dispersion in wages. In their basic calibration of a standard random search model, they obtained a mean-min ratio of 1.036 for wages, while their preferred empirical estimate is about 1.70 with a corresponding coefficient of variation of only 1/12th of the variation in the data.…”
Section: Appendix F: Wage Predictionsmentioning
confidence: 99%